7E Teaching Technique in Teaching and Learning Statistic for year II Students of Mathematics Section, Faculty of Education, Souphanouvong University - THIPPHAPHONE, Kinnaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
The research is to focus on teaching-learning of Statistic Subject by using 7E teaching methodology. The objective of research is to study the efficiency of teaching plan according to criteria 70/70, to study the effective of students’ learning, to compare the study’s result on pretest and posttest, and to study the students’ satisfaction for teaching 7E. The simple group is 41 students in year two of Mathematics Teacher Programme in Souphanouvong University and simple group was selected by simple random by selecting label of room for simple group. The equipment of research consists of five teaching plans of statistic subject and each teaching plan use two hours to process teaching-learning. The test form for learning achievement assessment is the four choice questionnaires in 20 questionnaires. There are the implementation and behavior evaluation form, sub-test form and 20 questionnaires for satisfaction evaluation. The Index Of Item Objective (IOC) of teaching plan and questionnaires are between 0.66-1.00; the difficulty value (p) is between 0.49-0.76; the range value (r) is between 0.24-0.78; the reliability value of test paper is 80.54% and reliability of questionaires are 81.70%. The result of research as follow: 1) The value of efficiency of teaching plan of statistic subject by using 7E teaching methodology for student year two of mathematic teacher programme in Souphanouvong University is 84.93/83.41 that are higher than critiria 70/70. 2) The effective index of the effective of statistic subject learning by using 7E teaching methodology for student year two of mathematic teacher programme in Souphanouvong University is totally 0.7601 or 76.01%. 3) The comparsion of pretest and posttest result from learning achievement for statistic subject by using 7E teaching methodology for students year two of mathematic programme in Souphanouvong University are different in accordance with statistic meaning in 0.05 in which accepted the assumption that result of students’ learning is higher than before learining. 4) The students satisfy teaching-learning on statistic subject by using 7 E teaching methodology for student year two of mathematic teacher programme in Souphanouvong University is totally in high level. Conclusion: teaching-learning statistic subject by using 7 E teaching methodology that was developed and available efficiency that can proceed teaching-learning to students effectively in which impact to high result of study and students are satisfied in high level.